2018
DOI: 10.28991/cej-0309117
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Simultaneous Phenol and Chromium Removal From Water Using Titanium Dioxide Photocatalyst

Abstract: Organic pollutants along with heavy metals and organic metal compounds may cause abnormal changes in physical and chemical parameters (acidity, alkalinity, salinity, color, smell and taste) of aquatic ecosystems and are among the serious threats of environmental health, especially the water resources. In this study, the effect of titanium dioxide photocatalyst with different concentrations (50, 100, 200, 500 and 1000 mg/l) on the simultaneous removal of phenol and heavy metal (chromium) from aqueous solution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Epidemiological studies show that high-level exposure to NO 2 in the air as a pollutant lead to increasing approximately 5-7% of the lung cancers among people (ex-smokers and non-smokers) 9 . Moreover, these studies reveal that a positive correlation between air pollutants such as NO 2 and adverse effects on human health such as changes in the kidney, liver, heart, and decrease resistance immunity to infectious diseases [10][11][12] . World Organization Health (WHO) reported that NO 2 associated with adverse effects such as increases in respiratory symptoms, asthma prevalence and incidence, cancer incidence, adverse birth outcomes and mortality 13 .…”
mentioning
confidence: 99%
“…Epidemiological studies show that high-level exposure to NO 2 in the air as a pollutant lead to increasing approximately 5-7% of the lung cancers among people (ex-smokers and non-smokers) 9 . Moreover, these studies reveal that a positive correlation between air pollutants such as NO 2 and adverse effects on human health such as changes in the kidney, liver, heart, and decrease resistance immunity to infectious diseases [10][11][12] . World Organization Health (WHO) reported that NO 2 associated with adverse effects such as increases in respiratory symptoms, asthma prevalence and incidence, cancer incidence, adverse birth outcomes and mortality 13 .…”
mentioning
confidence: 99%
“…Kontoudakis et al [52] removed copper from white wine by membrane filtration and recorded a significant reduction. Amongst the various nanoparticles, TiO 2 demonstrated a noticeable influence on the performance of the membranes for the removal of metal ions as reported from several studies [41,[53][54][55][56]. The introduction of 1.0 wt% TiO 2 into membrane matrix structure improves the hydrophilicity and makes the surface more negatively charged.…”
Section: Introductionmentioning
confidence: 90%
“…Hence, this inhibitory effect might also be due to the adsorption of phenanthrene by SDBS [48]. In addition, the SDBS also could be adsorbed onto the sediment to occupy the adsorption site [49][50][51][52].…”
Section: The Single Effect Of Salinity and Sdbsmentioning
confidence: 99%